Predicting spawning date of nyale worms (Eunicidae, Polychaeta) in the southern coast of Lombok Island, Indonesia - IMAM BACHTIAR; NAILA TASLIMAH BACHTIAR (Society for Indonesian Biodiversity, 2019)
Abstract. Bachtiar I, Bachtiar NT. 2019. Predicting spawning date of nyale worms (Eunicidae, Polychaeta) in the southern coast of Lombok Island, Indonesia. Biodiversitas 20: 971-977. Spawning of marine nyale worms has been an important component of Sasak tradition of Bau Nyale (fishing nyale) for centuries and a tourism icon of the District of Lombok Tengah since the 1990s. Nyale is a mixture of epitokies of 3-5 species of Polychaeta worms (mostly Palola spp.) for reproduction. At present, prediction of spawning date of the nyale worms is carried out traditionally that might not satisfy demand of tourism market. The present study is to develop a scientific-based method for predicting date of nyale worms spawning or nyale swarming. Since available data are scarce, development of the method of data collection mainly uses analogy from polychaetes and other invertebrate reproduction patterns and any available information from traditional customs. Three hypotheses were developed to generate prediction for 100 years, from 2000 to 2100, and then these prediction dates were verified using available data before 2018. In the past 9 years, there are two mismatches between scientific and traditional predictions, i.e., 2015 and 2017 spawnings, in favor of the new prediction method. The new scientific prediction method provides more objective and accurate date of nyale worm spawning than the traditional method. The present prediction also shows that split spawning dates, February and March, do not come to pass every year, as traditional nyale fishers generally believe them. It is also found that nyale worms are consistently using international lunar calendar for its spawning date, instead of local and national lunar calendars. This study provided the first scientific nyale swarming prediction in Lombok to complement existing traditional prediction. The prediction is very useful to promote the biggest annual traditional festival in Lombok for international visitors.